Програмні засоби використання track points у відео - Печенов, М. А. (ХНУРЕ, 2023)
In this paper, the role of tracking technology in the modern world, in particular in the field of cinematography, was analyzed, various tracking algorithms were considered, the use of various types of color difference markers was tested, and methodological recommendations were developed on the use of various tracking algorithms for narrowly focused tasks.
Keywords: відео